PENGEMBANGAN BAHAN AJAR DENGAN MODEL PEMBELAJARAN POGIL UNTUK MENINGKATKAN PRESTASI BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA - Yuniarto, Eko (FKIP Universitas Wisnuwardhana, 2018)
The development objective in this study is to produce a teaching material that is in accordance with the POGIL model on the subject of particle kinematics which can improve the learning achievement of mathematics education students in the Basic Physics lecture. Classes that use the POGIL model will run optimally when using appropriate learning materials. Suitable teaching materials are teaching materials that can present the concept of science in a systematic manner in accordance with the POGIL syntax.Â The output of this research can be published in his Likithaprad journal. Additional output targets for this development research can be published in nationally-accredited journals namely Education and Learning journals. The research method used for this research development refers to the Thiagarajan 4-D model. The 4-D model development procedure is used as a reference in this study with several reasons, including this development model is simpler, systematic, coherent, more specific and easy to follow the steps of development. In addition, the 4-D model specifically emphasizes the process of developing instructional materials and not on the learning design.Â The instructional material produced is expected to improve understanding and in accordance with the characteristics of students. In addition, the use of this teaching material can also increase the test scores of mathematics education students at Wisnuwardhana University Malang.Keywords: teaching materials, POGIL, student characteristics